Beginning Visual Web Developer 2005 Express From Novice to Professional - Delorme, Richard; Sarknas, Paul (Apress : Imprint: Apress, 2006)
The primary goal of this book is to demonstrate Visual Web Developer 2005 Expresss effectiveness when developing applications. The secondary goal is to examine how coding best-practices can be applied with this new product. Beginning Visual Web Developer 2005 Express provides a rigorous overview of the application: how it operates, how it compares to the other versions of Visual Studio .NET 2005 now available, and the best way to use it. The authors demonstrate techniques and concepts that you need to build working ASP.NET 2.0 applications. They use real applications based on VWDs Personal Web Starter Kit. They also compare and contrast VWD and VS .NET, and discuss how to overcome difficulties when moving from one to the other. The books practical and goal-oriented discussion helps you maximize VWD Express as quickly as possible. This book does not assume any prior coding knowledge, so hobbyists and students alike will be able to glean valuable information from it.